2019
DOI: 10.1097/ee9.0000000000000076
|View full text |Cite
|
Sign up to set email alerts
|

Ambient air pollution and lung cancer risk among never-smokers in the Women's Health Initiative

Abstract: Background: Ambient air pollution is classified as a human carcinogen by the International Agency for Research on Cancer (IARC). However, epidemiologic studies supporting this classification have focused on lung cancer mortality rather than incidence, and spatial and temporal resolutions of exposure estimates have varied considerably across studies. Methods: We evaluated the association of outdoor air pollution and lung cancer incidence among never-smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The association between ambient NO 2 and lung cancer has regularly been observed [ 16 , 19 , 23 26 , 29 32 , 50 , 51 ], although not in all studies [ 27 , 28 ]. In regions with low NO 2 , significant associations with lung cancer have been found in studies conducted in the Netherlands [ 23 – 25 ], the UK [ 50 ], the USA [ 26 ], and Canada [ 16 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between ambient NO 2 and lung cancer has regularly been observed [ 16 , 19 , 23 26 , 29 32 , 50 , 51 ], although not in all studies [ 27 , 28 ]. In regions with low NO 2 , significant associations with lung cancer have been found in studies conducted in the Netherlands [ 23 – 25 ], the UK [ 50 ], the USA [ 26 ], and Canada [ 16 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association between other pollutants and lung cancer is less clear. Significant associations between nitrogen dioxide (NO 2 ) and lung cancer have been identified in regions in Europe [ 23 – 25 ], and North America [ 16 , 19 , 26 ], but the data are not consistent [ 14 , 27 , 28 ]. No associations were observed for studies conducted in China [ 29 ], Korea [ 30 , 31 ], and Iran [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study in never‐smoking women found an increased risk of lung cancer when comparing individuals with residences less than 50 versus greater 200 m from a highway [18]. The authors suggest that proximity to major roadways can lead to carcinogenic exposures, though not via elevated PM 2.5 or NO 2 levels [18]. Similar investigations emphasize particulate matter as an important contributor to lung cancer, especially in patients who never smoked.…”
Section: Discussionmentioning
confidence: 99%
“…There were no differences between patients who smoked and never smoked for distance to major roadway, daily average PM 2.5 , greenspace within 500 m, and distance to our medical center. One study in never‐smoking women found an increased risk of lung cancer when comparing individuals with residences less than 50 versus greater 200 m from a highway [18]. The authors suggest that proximity to major roadways can lead to carcinogenic exposures, though not via elevated PM 2.5 or NO 2 levels [18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, women in all developing countries, and particularly in East and South Asian countries, are exposed to polycyclic aromatic hydrocarbons, which are associated with lung cancer, as result of using cooking oil and other biomass fuels in poorly ventilated areas. Regarding environmental air pollution, the relationship between particulate matter air pollution exposure and lung cancer has been analyzed in two cohorts: the Nurses' Health Study Cohort (15,16), and the Women' s Health Initiative (17). These studies showed an increased risk of incident lung cancer associated with ambient particulate matter exposures and with residential proximity to major roads among neversmoker women.…”
Section: Smokingmentioning
confidence: 99%